KOLABORASI DAN INOVASI DALAM PENDIDIKAN KEJURUAN: STRATEGI PENGUATAN SPIRIT ENTREPRENEURSHIP BAGI SISWA SMK DI JAWA TIMUR - Sutanto, J.E; Sutrisno, Timotius Febry Christian Wahyu Sutrisno; Wibowo, Otje Herman; Winarno, Prasetyo Sepsi (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2025)
The open unemployment rate (TPT) in East Java is still dominated by graduates of Vocational High Schools (SMK), which shows a gap between the skills taught in schools and the needs of the workforce. This study aims to analyze the influence of entrepreneurial and culinary aspects on the readiness of vocational high school students to become entrepreneurs. Using a quantitative approach, data were collected from six vocational high schools in East Java that have Culinary, Agribusiness, and Marketing majors, with a closed questionnaire-based survey method using a Likert scale. The results of the study showed that entrepreneurial aspects, such as creativity, innovation, and courage to take risks, had a positive and significant effect on students' readiness to become entrepreneurs. Likewise, culinary aspects that include production skills, business management, and marketing strategies also increase students' readiness to build independent businesses. The implementation of